The Effect of Temperature and Fermentation Duration on pH Level and Vitamin C Content of Butterfly Pea Flower (Clitoria ternatea L.) Kombucha - Setyaji, Andy Anggoro; Fitriana, Adita Silvia; Samodra, Galih (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
Kombucha is produced through the fermentation of a tea and sugar mixture with a symbiotic culture of bacteria and yeast (SCOBY). It contains various compounds beneficial to health, including vitamin C. The pH level and vitamin C content of kombucha are affected by fermentation temperature and time. Correspondingly, this study aimed to determine the effects of temperature and fermentation duration on the pH level and vitamin C content of butterfly pea kombucha. The research was conducted employing laboratory experimental methods, including a UV-Vis spectrophotometer to measure vitamin C content and a digital pH meter to measure pH levels. The limit of detection (LoD) and the limit of quantification (LoQ) values for the UV-Vis spectrophotometer were 0.115 ppm and 3.77 ppm, respectively. The results indicated that fermentation temperature did not affect the pH or vitamin C content. However, the pH level was affected by fermentation time, while vitamin C content was not statistically affected. The highest pH value (5.11) was observed on day 0 of fermentation, and the highest vitamin C content (2.94%) was recorded on day 6 at a temperature of 30°C.